The Social Prioritization Index and Tobacco Use Among Young Adult Bar Patrons. (December 2016) - Lisha, Nadra E.; Neilands, Torsten B.; Jordan, Jeffrey W.; Holmes, Louisa M.; Ling, Pamela M.
Social benefits likely play a role in young adult tobacco use. The Social Prioritization Index (SPI) was developed to measure the degree to which young adults place a great importance on their social lives. We examined the usefulness of this measure as a potential predictor of tobacco use controlling for demographics and tobacco-related attitudes. Young adults completed cross-sectional surveys between 2012 and 2014 in bars in seven U.S. cities ( N = 5, 503). The SPI is a 13-item scale that includes personality items and information on how frequently participants attend bars and how late they stay out. Three step-by-step multinomial regression models were run using the SPI as a predictor of smoking status (nondaily and daily smoking vs. nonsmoking): (1) SPI as the sole predictor, (2) SPI and demographics, and (3) SPI, demographics, and tobacco-related attitude variables. Next, we conducted an exploratory factor analysis to examine if the number of items in SPI could be reduced and retain its strong relationship with smoking. Higher scores on the SPI were related to an increased probability of being a Nondaily Smoker (odds ratio = 1.09, 95% confidence interval [1.04, 1.14], p < .001) or Daily Smoker (odds ratio = 1.14, 95% confidence interval [1.07, 1.22], p < .0001) compared to a Nonsmoker, controlling for demographics and other tobacco-related attitudes. The SPI and reduced SPI were independently related to young adult tobacco use. The measure's brevity, ease of use, and strong association with tobacco use may make it useful to tobacco and other prevention researchers.